Emerging topologies of transnational employment: 'Posting' Thai workers in Sweden's wild berry industry beyond regulatory reach. Issue 89 (February 2018) - Axelsson, Linn; Hedberg, Charlotta
Highlights: Employment is increasingly stretched across several regulatory regimes. Adopts a topological approach to examine precarious working conditions of transnationally mobile migrant workers. Transnational subcontracting reconfigures employment in a spatial sense. It is difficult to protect the interests of transnationally mobile labour through national legislative frameworks. Abstract: This paper suggests a need to pay closer attention to the fact that employment is increasingly stretched across several regulatory regimes. This may help explain why governments, which rely on national legislative frameworks, struggle to protect the interests of transnationally mobile low-skilled workers. By adopting a topological approach to state regulation and authority, the paper demonstrates how powerful actors have reconfigured employment in Sweden's wild berry industry in a spatial sense by engaging transnational subcontractors. It argues that transnational subcontracting inserts distance into employment relationships, thereby creating precarious migrant workers whose simultaneous absence and presence in several regulatory regimes places them partly beyond the regulatory reach of any one nation-state or nationally based trade union. The paper also argues that the Swedish government's response to precarious working conditions in the wild berry industry can be understood as a series of attempts aimed at bringing transnational employment relationships within its regulatory reach. Drawing on topological spatial vocabulary, it shows how these attempts are less about the movement of state infrastructure into transnational space than about the stretching and folding of space itself, in an attempt to establish a powerful Swedish presence across distance. On the other hand, the paper concludes that transnational subcontracting opens up a space which enables wild berry actors to circumvent regulations and, as such, it remains very difficult for the Swedish government to reach into employment relationships in this industry.